Fibrovascular Polyps of the Hypopharynx: A Case Report - Herdini, Camelia; Wirata, I Komang Praba Edi; Indrasari, Sagung Rai; Yudistira, Danu; Alamanda, Monik (Indonesian Journal of Cancer, 2025)
Introduction: Fibrovascular polyps are very rare, non-cancerous growths in the hypopharynx, though they can occur anywhere in the pharynx. Surgical excision is the definitive treatment to alleviate the patient's symptoms with an excellent outcome. This case report aims to share knowledge about the clinical presentation and treatment of this rare condition. Case Presentation: A 45-year-old man complained primarily of recurrent sore throat and frequent choking episodes, particularly during sleep. He also felt a mass in his deep throat, which he felt in his mouth just before swallowing, particularly when he vomited. A pedunculated mass originating from the lateral hypopharyngeal wall is detected during physical examination. After the mass was completely resected, he received proton pump inhibitors (PPI) and postoperative antibiotics.Conclusion: For fibrovascular polyps, definitive surgical excision is the preferred treatment. It is recognized that with total resection, malignant transformation and disease recurrence are relatively rare.